Response of wheat to Azotobacter, nitrogen and sulphur application in an alluvial soil - Singh, Harvendra; Bhadoria, Harendra Singh (Annals of Agricultural Research, 2016)
A field experiment was conducted at Gwalior (M.P.) to evaluate the response of Azotobacter, nitrogen and sulphur on wheat during rabi seasons of 2008-10. Results revealed that seed inoculation with Azotobacter increased the grain and straw yield of wheat in both the crop seasons. Application of nitrogen up to 150 kg /ha increased the grain yield by 26.9 and 28.0 per cent over 75 kg N/ha in first and second year, respectively. Application of S up to 25 kg/ ha enhanced the mean grain yield by 12.5 per cent over control. Similar trend in yield response of straw was recorded. The mean total uptake of S progressively increased from 19.0 to 29.5 kg / haÂ  with the 25 kg S / ha. The uptake of nitrogen also increased with the levels of N application. The uptake of N, P and S increased with the application of S and Azotobacter inoculation. Azotobacter inoculation improved the status of available nitrogen in soil over initial value. Available N in soil increased with increasing levels of N and S. Similarly, application of sulphur improved its build up in soil. Organic carbon status in soil improved with Azotobacter, N and S application.